Supramolecular hydrogels of β-cyclodextrin linked to calcium homopoly-L-guluronate for release of coumarins with trypanocidal activity - Moncada-Basualto, M.; Matsuhiro, B.; Mansilla Muñoz, Andres Omar; Lapier, M.; Maya, J. D.; Olea-Azar, C. (My University, 2019)
Association constants and thermodynamicsparameters on inclusion of four 3-amido coumarins that present trypanocidal activity, into 6-amino-beta-cyclodextrin (1: 1 stoichimetry) were determined. In addition, pure homopolymeric-a-L-guluronate fraction prepared by partial hydrolysis of sodium alginate from Sub-Antarctic Kelp Durvillaea antarctica was conjugated with 6-amino-beta-cyclodextrin (64% yield). To glycoconjugates, 3-amido coumarins were incorporated (73% of encapsulation) and supramolecular hydrogels were prepared by gelation with Ca2+ ions. The trypanocidal activity of the inclusion complexes increased by 10%. Likewise, an increase in diffusion in artificial membrane was observed (13%). It was found that the inclusion complexes increased the variation of the mitochondrial potential of T. cruzi (17%). The lowest release of substituted amidocoumarins (ACS) from supramolecular hydrogels occurred at pH 1.2 whereas the maximum release (34%) was observed at pH 8.0. Encapsulation of lipophilic bioactive compounds in supramolecular hydrogels allows the generation of release systems sensitive to pH with potential application in biomedicine.
Keywords: homopoly-l-guluronate; 3-amidocoumarins; inclusion complex; trypanosoma cruzi; supramolecular hydrogel; sub-antarctic macroalgae